Dilema E-Democracy di Indonesia: Menganalisis Relasi Internet, Negara, dan Masyarakat - Ahmad Alwajih (Program Studi Ilmu Komunikasi, 2014)
Implementation of e-democracy in Indonesia is still problematic. This notions based on three arguments which is discussed in this article. First, e-democracy is just the facilities or the goals? Second, define e-democracy as a facilities or goals of democracy, leads to question, how this new system of democracy could be start, from structure or culture of society? Third, if Indonesians digital culture has established, then internet as democracy space could be examined, does this necessarily make the internet as a public sphere, as Jurgen Habermas theory said? This article does not aim for a practical solution, but rather try to analyze and mapping out some of the indecision in the implementation of e-democracy in Indonesia, so that the various tensions between internet relations, state , and society can be clearly explained.